2020
DOI: 10.1007/s10433-020-00559-6
|View full text |Cite
|
Sign up to set email alerts
|

The gender health gap in Europe’s ageing societies: universal findings across countries and age groups?

Abstract: We provide a systematic country and age group comparison of the gender gap in several generic health indicators and more specific morbidity outcomes. Using data from the Survey of Health, Ageing and Retirement (SHARE), we examined the gender gap in the prevalence of poor self-rated health, chronic health conditions, activity limitations, multimorbidity, pain, heart attacks, diabetes, and depression in three age groups (50-64, 65-79, and 80+) based on linear probability models with and without adjustment for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
(59 reference statements)
3
14
0
Order By: Relevance
“…Gender-based health inequality in older age has been reported in studies in European countries and the USA. Although the level of inequality differs from one country to another, women on average display a worse health status than men (Schmitz and Lazarevič 2020 ). Our study confirms such a gender difference: Chinese older women are significantly less likely than men to achieve healthy ageing.…”
Section: Discussionmentioning
confidence: 99%
“…Gender-based health inequality in older age has been reported in studies in European countries and the USA. Although the level of inequality differs from one country to another, women on average display a worse health status than men (Schmitz and Lazarevič 2020 ). Our study confirms such a gender difference: Chinese older women are significantly less likely than men to achieve healthy ageing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature also reports conflicting associations between sex and the clinical severity of OA ( 42 ). Data from the European SHARE cohort reveal that women have overall disadvantages in terms of activity limitations, pain, depression, and self-reported health status compared with men ( 43 ). On the other hand, a systematic review by Bastick et al found strong evidence that sex is not associated with radiographic severity ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Serrano-Alarcón and Perelman ( 44 ) found that women 65–79 years old in Spain, Portugal, and Italy were 3.3% more likely than men to have severe function limitations; increasing the age bracket to those age 80 or older increased this likelihood to 15.5%. A recent study spanning 16 European countries found that gender disparities in activity limitations that disfavored women were larger in southern Europe and generally increased with age; however, these trends were not universally present in every country studied ( 45 ). Moreover, a systemic review of 21 longitudinal studies conducted mostly in high-income countries failed to show a consistent gender difference in the incidence of functional disability ( 18 ).…”
Section: Discussionmentioning
confidence: 90%